Bible Vs Anxiety Disorder: Analisis Konteks Amsal 3:5-10 dalam Integrasi Teologi-Psikologi - Siburian, Herbet Alfredo; Triyanto, Yoel (Sekolah Tinggi Teologi Jaffray Jakarta, 2023)
The Book of Proverbs is a book of wisdom in the Old Testament which is quite complex in its poetic language. Readers of Proverbs often offend the empty space in the soul and spirituality of Christian readers. Proverbs 3:5-10 forbids fear and obedience to God in His majesty. The reality is that people still respond to obedience to God with anxiety. In human anxiety sometimes, do not even realize they are hurting themselves, thus causing anxiety disorders. Therefore, humans must firmly rely on God in their journey of life. This paper is reviewed with an analysis of context and grammar in the integration of theology and psychology. Therefore, the writer will expose Proverbs 3:5-10 into 3 parts, namely verses 5-6, 7-8, and 9-10. The exposition aims to describe the new meaning of the text that is formed in the re-reading of Proverbs 3:5-10 which is related to one's psychological anxiety.